Alpha-Gal Syndrome: Involvement of Amblyomma americanum α-D-Galactosidase and β-1,4 Galactosyltransferase Enzymes in α-Gal Metabolism - Sharma, Surendra Raj; Crispell, Gary; Mohamed, Ahmed; Cox, Cameron; Lange, Joshua; Choudhary, Shailesh; Commins, Scott P.; Karim, Shahid (Frontiers in Cellular and Infection Microbiology, 2021)
Alpha-Gal Syndrome (AGS) is an IgE-mediated delayed-type hypersensitivity reaction to the oligosaccharide galactose-⍺-1,3-galactose (α-gal) injected into humans from the lone star tick (Amblyomma americanum) bite. This study aims at the functional characterization of two tick enzymes, α-D-galactosidase (ADGal) and α-1,4 galactosyltransferase (β-1,4GalT) in α-gal metabolism. The ADGal enzyme cleaves terminal α-galactose moieties from glycoproteins and glycolipids, whereas β-1,4GalT transfers α-galactose to a β1,4 terminal linkage acceptor sugars: GlcNAc, Glc, and Xyl in various processes of glycoconjugate synthesis. An RNA interference approach was utilized to silence ADGal and β-1,4GalT in Am. americanum to examine their functional role in α-gal metabolism and AGS onset. Silencing of ADGal led to the significant down-regulation of genes involved in galactose metabolism and transport in Am. americanum. Immunoblot and N-glycan analysis of the Am. americanum salivary glands showed a significant reduction in ⍺-gal levels in silenced tissues. However, there was no significant difference in the level of ⍺-gal in β-1,4GalT silenced tick salivary glands. A basophil-activation test showed a decrease in the frequency of activated basophil by ADGal silenced salivary glands. These results provide an insight into the role of α-D-galactosidase & β-1,4GalT in tick biology and the probable involvement in the onset of AGS.